Wintertime Variations of Gaseous Atmospheric Constituents in Bucharest Peri-Urban Area - Cristina Antonia Marin; Luminiţa Mărmureanu; Cristian Radu; Alexandru Dandocsi; Cristina Stan; Flori Ţoancă; Liliana Preda; Bogdan Antonescu (Atmosphere, 2019)
An intensive winter campaign was organized for measuring the surface air pollutants in southeastern Europe. For a three months period, the gas concentrations of NO <semantics> x </semantics> , SO <semantics> 2 </semantics> , CO, O <semantics> 3 </semantics> , and CH <semantics> 4 </semantics> as well as meteorological parameters were simultaneously sampled to evaluate the variations and characteristic reactions between the gases during winter at the measuring site. The photochemical production of the ozone was observed through the diurnal variation of ozone and the solar radiation, the maximum concentration for ozone being reached one hour after the maximum value for solar radiation. A non-parametric wind regression method was used to highlight the sources of the air pollutants. The long-range transport of SO <semantics> 2 </semantics> and two hotspots for CO from traffic and from residential heating emissions were emphasized. The traffic hotspot situated north of the measuring site, close to the city ring road, is also a hotspot for NO <semantics> x </semantics> . The air quality during the cold season was evaluated by comparing the measured gas concentration with the European limits. During the measuring period, the values for NO <semantics> 2 </semantics> , CO, and SO <semantics> 2 </semantics> concentration were at least two times lower than the European Union pollution limits. Only twice during the study period was the concentration of O <semantics> 3 </semantics> higher than the established limits.